Total Endoscopic Transcatheter Mitral Valve-in-Valve Replacement with Concomitant Left Atrial Appendage Occlusion and Tricuspid Valve Repair - Hua Shen; Zekun Feng; Nan Cheng; Lin Zhang; Shengli Jiang (Cardiovascular Innovations and Applications)
A 75-year-old man with a history of coronary artery bypass grafting and mitral valve replacement presented with a degenerated mitral bioprosthesis, severe tricuspid regurgitation, and atrial fibrillation. Because of the high surgical risk, a minimally invasive total endoscopic approach was used. Left atrial appendage closure was performed under hypothermic ventricular fibrillation without aortic cross-clamping. Subsequent transcatheter mitral valve-in-valve implantation and concomitant tricuspid valve annuloplasty were successful. The procedure resulted in the restoration of normal mitral and tricuspid valve function, thereby demonstrating the feasibility and safety of this combined surgical approach.